Resistensi populasai hama bawang merah Spodoptera exigua (Lepidoptera: Noctuidae) terhadap klorfluazuron - Abdi Negara (Perhimpunan Entomologi Indonesia, 2005)
Resistance of Onion Pest Spodoptera exigua (Lepidoptera: Noctuidae) Populations to Chlorfluazuron. The research was conducted from August 2001 until April 2002 in the Kalitiro Agriculture Training and Development Research Station, Gadjah Mada University. The objective of research was to determine the resistance level of Spodoptera exigua populations collected from the district of Sanden, Kretek, Wates, Temon, Panjatan, Wonosari, Panggang and Playen (all are in Yogyakarta Province) to chlorfluazuron insecticide. Research was conducted by dipping artificial diet about 30 seconds in insecticide solution and there are used test two hours after they were air dried. Based on the preliminary test, different concentrations were tested to determine the toxicity of the insecticide to each population. Third instar larvae (five days old) of the first generation were used in bioassays. Each larvae with its artificial diet was placed in a plastic cup (diameter 3,5 cm). Larval mortality was recorded at 72 hours after exposure. Data was analyzed using probit analysis to determine LC50 values. The result showed that the LC50 values of chlorfluazuron againsts eight population of S. exigua at 72 hours after exposure varied from 16,10 ppm (Panggang) to 84,76 ppm (Panjatan). The results suggested that all populations from Panggang, Playen, Kretek, Sanden, Wates, Wonosari and Temon were still susceptible to chlorfluazuron. Population from Panjatan indicated to be resistant to chlorfluazuron.